Estimate Complete the Survival Function for Real Data of Lung Cancer Patients - Salman, Abbas N.; Farhan, Ibtehal H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we estimate the survival function for the patients of lung cancer using different nonparametric estimation methods depending on sample from complete real data which describe the duration of survivor for patients who suffer from the lung cancer based on diagnosis of disease or the enter of patients in a hospital for period of two years (starting with 2012 to the end of 2013). Comparisons between the mentioned estimation methods has been performed using statistical indicator mean squares error, concluding that the survival function for the lung cancer by using shrinkage method is the best